INTEGRATING PERSUASION AND EXEMPLARY LEADERSHIP: AN ISLAMIC COMMUNICATION MODEL FROM INDONESIAN ISLAMIC BOARDING SCHOOLS - Muhammad Ihsan Hayatuddin; Elhefni Elhefni; Candra Darmawan (Jurnal Konseling Pendidikan Islam, 2026)
This study is part of the discourse on Islamic communication and Islamic boarding school education in Indonesia, focusing on the construction of communication models in shaping the character of Islamic boarding school students. This study aims to formulate an integrative Islamic communication model that combines normative persuasion, leadership exemplarity, and religious culture as a moral guidance system at the Raudhatul Qur'an Payaraman Islamic Boarding School. The study uses a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and document analysis. Informants were selected purposively based on their strategic roles in the educational process. Data analysis techniques used an interactive model through data reduction, data presentation, and cyclical conclusion drawing, with validity reinforced through source and method triangulation. The results show that Islamic communication in Islamic boarding schools takes place systematically and relationally. Persuasion shapes the cognitive framework of values, exemplarity presents moral legitimacy through consistency of action, while religious culture reproduces values through routines and social structures. The integration of these three elements forms a mechanism for the internalization of akhlakul karimah that is cyclical and sustainable. This study produced an integrative Islamic communication model based on a cultural systemic approach as a conceptual and strategic reference in character building in Islamic educational institutions.